2007
DOI: 10.1189/jlb.0506359
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin-cleaved Bid promotes apoptosis in human neutrophils via oxidative stress-induced lysosomal membrane permeabilization

Abstract: Lysosomal membrane permeabilization (LMP) is emerging as an important regulator of cell apoptosis. Human neutrophils are highly granulated phagocytes, which respond to pathogens by exhibiting increased production of reactive oxygen species (ROS) and lysosomal degranulation. In a previous study, we observed that intracellular, nonphagosomal generation of ROS triggered by adherent bacteria induced ROS-dependent neutrophil apoptosis, whereas intraphagosomal production of ROS during phagocytosis had no effect. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
139
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 51 publications
(76 reference statements)
11
139
0
Order By: Relevance
“…In this model of apoptosis induction, PyMT;Ctsb À/À tumour cells were found to be significantly more resistant to Leu-LeuOMe than the control PyMT tumour cells. This could be (Stoka et al, 2001;Cirman et al, 2004;Blomgran et al, 2007;Nagaraj et al, 2007). Taken together, our results suggest that absence of Ctsb in primary PyMT tumour cells does not alter their susceptibility to an inducer of tumour cell apoptosis, that is TNF-a.…”
Section: Discussionsupporting
confidence: 64%
“…In this model of apoptosis induction, PyMT;Ctsb À/À tumour cells were found to be significantly more resistant to Leu-LeuOMe than the control PyMT tumour cells. This could be (Stoka et al, 2001;Cirman et al, 2004;Blomgran et al, 2007;Nagaraj et al, 2007). Taken together, our results suggest that absence of Ctsb in primary PyMT tumour cells does not alter their susceptibility to an inducer of tumour cell apoptosis, that is TNF-a.…”
Section: Discussionsupporting
confidence: 64%
“…As shown in Fig. 6B, the respiratory burst induced by Mtb was weaker (<15%) than that elicited by an E. coli strain (FimH+, expressing type 1 fimbriae), previously reported to cause strictly ROS-dependent apoptosis [12].…”
Section: 5mentioning
confidence: 60%
“…It has been shown that ROS produced during cell activation is a mediator of apoptosis in inflammatory cells [12,21]. Using luminol-amplified chemiluminescence, we measured formation of ROS in PMNs and found that both opsonized and unopsonized Mtb induced similar amount of ROS (Fig.…”
Section: 5mentioning
confidence: 81%
See 2 more Smart Citations